Chlorhexidine gluconate bathing in children with cancer or those undergoing hematopoietic stem cell transplantation: A double‐blinded randomized controlled trial from the Children's Oncology Group. Issue 1 (20th October 2020) - Zerr, Danielle M.; Milstone, Aaron M.; Dvorak, Christopher C.; Adler, Amanda L.; Chen, Lu; Villaluna, Doojduen; Dang, Ha; Qin, Xuan; Addetia, Amin; Yu, Lolie C.; Conway Keller, Mary; Esbenshade, Adam J.; et al.
Abstract : Background: To the authors' knowledge, information regarding whether daily bathing with chlorhexidine gluconate (CHG) reduces central line–associated bloodstream infection (CLABSI) in pediatric oncology patients and those undergoing hematopoietic stem cell transplantation (HCT) is limited. Methods: In the current multicenter, randomized, double‐blind, placebo‐controlled trial, patients aged ≥2 months and <22 years with cancer or those undergoing allogeneic HCT were randomized 1:1 to once‐daily bathing with 2% CHG‐impregnated cloths or control cloths for 90 days. The primary outcome was CLABSI. Secondary endpoints included total positive blood cultures, acquisition of resistant organisms, and acquisition of cutaneous staphylococcal isolates with an elevated CHG mean inhibitory concentration. Results: The study was stopped early because of poor accrual. Among the 177 enrolled patients, 174 were considered as evaluable (88 were randomized to the CHG group and 86 were randomized to the control group). The rate of CLABSI per 1000 central line days in the CHG group was 5.44 versus 3.10 in the control group (risk difference, 2.37; 95% confidence interval, 0.05‐4.69 [ P = .049]). Post hoc conditional power analysis demonstrated a 0.2% chance that the results would have favored CHG had the study fully enrolled. The rate of total positive blood cultures did not differ between groups (risk difference, 2.37; 95% confidence interval, −0.41 to 5.14 [ P = .078]). The number of patients demonstrating the new acquisition of resistant organisms did not differ between groups ( P = .54). Patients in the CHG group were found to be more likely to acquire cutaneous staphylococcal isolates with an elevated CHG mean inhibitory concentration ( P = .032). Conclusions: The data from the current study do not support the use of routine CHG bathing in children with cancer or those undergoing allogeneic HCT. Abstract : In this randomized clinical trial of 177 children with cancer or those undergoing hematopoietic stem cell transplantation, chlorhexidine gluconate (CHG) bathing does not appear to reduce central line–associated bloodstream infection, total positive blood cultures, or the acquisition of resistant organisms. The results do not support the routine use of CHG bathing in this population.